2002
DOI: 10.1083/jcb.200112067
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus triggers macropinocytosis and endosomal leakage together with its clathrin-mediated uptake

Abstract: Adenovirus type 2 (Ad2) binds the coxsackie B virus Ad receptor and is endocytosed upon activation of the αv integrin coreceptors. Here, we demonstrate that expression of dominant negative clathrin hub, eps15, or K44A-dynamin (dyn) inhibited Ad2 uptake into epithelial cells, indicating clathrin-dependent viral endocytosis. Surprisingly, Ad strongly stimulated the endocytic uptake of fluid phase tracers, coincident with virus internalization but without affecting receptor-mediated transferrin uptake. A large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
417
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(439 citation statements)
references
References 67 publications
17
417
2
3
Order By: Relevance
“…Other viruses have also been observed to co-localize with CCPs in live cells, including reovirus and adenovirus 30,31 . In common with Influenza, reovirus enters by the de novo formation of CCPs 30 .…”
Section: Viral Entrymentioning
confidence: 99%
“…Other viruses have also been observed to co-localize with CCPs in live cells, including reovirus and adenovirus 30,31 . In common with Influenza, reovirus enters by the de novo formation of CCPs 30 .…”
Section: Viral Entrymentioning
confidence: 99%
“…Studies on Ad-host interactions found that cytosolic release of macropinosomal contents may be triggered by receptor signaling. 91 While other types of cell entry pathways exist, some of which are little understood, those just described earlier have been identified as largely contributing to the uptake of numerous types of nonviral vectors. To delineate these cell entry pathways for the uptake of a particular vector, trafficking inhibitors, in addition to trafficking markers and special cell lines, can be used.…”
Section: Intracellular Trafficking Of Nonviral Vectors Lk Medina-kauwmentioning
confidence: 99%
“…Other pathways have, however, been suggested, 40,41 and adenoviral particles have been observed in vesicles without clathrin coating and in macropinosomes. The enhanced gene transfer after photochemical treatment could be due to the release of the viral particles from any of these vesicles.…”
Section: Discussionmentioning
confidence: 99%